PIANO NAZIONALE RESIDUI 2016-2017: ESAME E VALUTAZIONE DELL’EFFICACIA DEL PIANO (Rassegna di Diritto, Legislazione e Medicina Legale Veterinaria, 2018)
The Authors examine the national residual plan for 2016 (Italian Health Minister), through a comparison using the data collected in the year 2017. Conducting an analysis carried out through statistical-epidemiological investigation at some slaughter houses in the province of Vicenza, the Authors re-evaluate the effectiveness of the plan in relation also to the regulatory framework at Community, national and regional level